2021
DOI: 10.1016/j.jsxm.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Sexual Behaviors in Undergraduate Students: Findings From a Campus Probability Survey

Abstract: Background Probability-based surveys of college students typically assess sexual behaviors such as oral, vaginal, and anal sex. Little is known about the broader range of sexual behaviors in which students engage. Aims In a random sample survey of undergraduate students, we aimed to: (1) describe how recently participants had engaged in solo and partnered sexual behaviors, (2) examine how frequently participants enacted certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…However, this finding is also in contrast to previous research, which has found that those with older age were more represented in BDSM communities (Alison et al, 2001). Together, the absence of educational level and gender differences, and the reversal of the age association could be indicative of the general mainstreaming of BDSM (Andrieu et al, 2019;Simula, 2019;Sisson, 2007;Weiss, 2006) that has occurred in recent years, especially considering that BDSMrelated sexual activities are found to be relatively prevalent in college-age populations (Herbenick et al, 2021). Conversely, our findings that more of the younger populations were BDSM-oriented than older participants (which differs from previous studies) may be due to methodological differences, as this study was conducted online and earlier studies were often conducted in person or recruited participants through BDSM clubs.…”
Section: Demographic Characteristics Of the Bdsm Participantscontrasting
confidence: 75%
“…However, this finding is also in contrast to previous research, which has found that those with older age were more represented in BDSM communities (Alison et al, 2001). Together, the absence of educational level and gender differences, and the reversal of the age association could be indicative of the general mainstreaming of BDSM (Andrieu et al, 2019;Simula, 2019;Sisson, 2007;Weiss, 2006) that has occurred in recent years, especially considering that BDSMrelated sexual activities are found to be relatively prevalent in college-age populations (Herbenick et al, 2021). Conversely, our findings that more of the younger populations were BDSM-oriented than older participants (which differs from previous studies) may be due to methodological differences, as this study was conducted online and earlier studies were often conducted in person or recruited participants through BDSM clubs.…”
Section: Demographic Characteristics Of the Bdsm Participantscontrasting
confidence: 75%
“…Lastly, we restricted participant eligibility to female students, reducing the applicability of these preliminary findings to men, but this decision was supported by two reasons. Previous literature suggests being choked/strangled, both in cases of IPV and as a partnered sexual behavior, is highly gendered, with significantly more women being choked/strangled as compared to men (McClane et al, 2001 ; Herbenick et al, 2021e ). Additionally, sex differences have been reported in working memory behavioral performance (Voyer et al, 2017 , 2021 ) and fMRI activation during working memory tasks (Bell et al, 2006 ; Zilles et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As awareness of choking/strangulation as a partnered sexual behavior has entered mainstream conversations, questions concerning the safety and long-term psychological and neurologic consequences of being choked/strangled in this context have been raised (Herbenick et al, 2021e ). Recent and frequent exposure to being choked has been linked to worse mental health in a recent probability survey of undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from the United States, United Kingdom, and Germany demonstrates that sexual choking/strangulation has become prevalent among young adults, disproportionately affects women, often begins in adolescence, and is frequently first learned about through pornography, social media, partners, and friends (Herbenick et al, 2020(Herbenick et al, , 2021c(Herbenick et al, , 2022bSavanta Com Res, 2019;Sun et al, 2017;Wright et al, 2015). In a random sample survey of 4,989 U.S. college students, 58% of women had ever been choked during sex, and one quarter of women were first choked by age 17 (Herbenick et al, 2021c). In New Zealand, sexual choking has been identified as a growing trend among youth (Beres et al, 2020).…”
Section: Introductionmentioning
confidence: 99%